Digital Leadership And ISO 31000 Integration For Sustainable Organizational Resilience: A Systematic Review And The SRRIM - Abadi, Ahmad; Adinata, Junaidi; Negara, Roberto Surya; Hutagaol, Poltak Maruli John Liberty (Dinasti Publisher, 2026)
This study constructs the Sustainable Risk-Resilience Integration Model (SRRIM) to explicate how digital leadership integrates ISO 31000 into an adaptive socio-technical system of governance to develop Sustainable Organizational Resilience (SOR). This study explains the socio-managerial processes that connect digital leadership, risk management, and sustainability in terms of organizational behavior and risk interdependence. It adopts a hybrid approach of analysis based on inductive content analysis, abductive inference, and the hermeneutic circle of Heidegger to integrate the multidisciplinary literature, as well as to develop an explanatory conceptual model. Results indicate a serial mediation process where digital leadership creates a collaborative digital risk sensemaking culture, promotes dynamic human and structural risk reconfiguration, and presupposes adaptive risk governance. This approach unites risk-based sustainability and sustainability-based risk management to make ISO 31000 a dynamic organizational capability rather than merely an administrative compliance framework. The model also determines the intensity of risk interdependence as a boundary condition that reinforces or weakens the indirect impact on SOR. In theory, this paper incorporates the dynamic capabilities and institutional theory into a mechanism-based framework, which conceptually directs organizations in planning digital risk management to increase human capacity, long-term resilience, and sustainability.